Radioimmunotherapy is More Effective than Antifungal Treatment in Experimental Cryptococcal Infection - Bryan, Ruth A. (2010)
Radioimmunotherapy (RIT) prolongs survival of mice infected with Cryptococcus neoformans (CN). To compare the efficacy of RIT and amphotericin B, we infected AJCr mice IV with either non-melanized or melanized CN cells. Infected mice were either left untreated, treated 24 hours post infection with (213)Bi-18B7 antibody or amphotericin or both. Melanization before infection did not increase resistance of CN to RIT in vivo. (213)Bi-18B7 treatment almost completely eliminated lung and brain CFUs while amphotericin did not decrease CFUs. We conclude that RIT is more effective than amphotericin against systemic infection with CN.